Detection of selected pathogens in ticks collected from cats and dogs in the Wrocław Agglomeration, South-West Poland. Issue 1 (December 2016) - Król, Nina; Obiegala, Anna; Pfeffer, Martin; Lonc, Elżbieta; Kiewra, Dorota
Abstract Background Tick-borne infections are no longer confined to rural areas, they are documented with increasing frequency in urban settlements across the world. They are known to cause diseases in humans as well as in their companion animals. Methods During a period of 2 years, from January 2013 until December 2014, ticks were collected from dogs and cats in 18 veterinary clinics in the Wrocław Agglomeration, Poland. In total, 1455 ticks were found on 931 pets: 760 domestic dogs and 171 cats. For molecular examinations 127I. ricinus ticks (115 females and 12 males) were randomly selected, all collectedI. hexagonus (n = 137, 32 females, 98 nymphs, 7 larvae) and all collectedD. reticulatus (n = 46, 31 females, 15 males) were taken.Ixodes ricinus andI. hexagonus ticks were tested forRickettsia spp., Anaplasma phagocytophilum, Candidatus Neoehrlichia mikurensis andBabesia spp., whileD. reticulatus ticks were investigated forRickettsia spp. andBabesia spp. only. Results In total, 65.4 %I. ricinus ticks were infected with at least one pathogen. Over 50 % ofI. ricinus were positive forRickettsia spp. (R. helvetica andR. monacensis ). The infection level withA. phagocytophilum was 21.3 %. DNA ofCand . N. mikurensis was detected in 8.1 %I. ricinus ticks. Interestingly only female ticks were infected. The prevalence ofBabesia spp. was confirmed in 9.0 % ofI. ricinus involving the speciesB. microti andB. venatorum. A total of nineteen double, one triple and two quadruple infections were found inI. ricinus ticks only. Almost 11 % ofI. hexagonus ticks were positive for at least one of the tested pathogens.Rickettsia spp. infection was found in 2.2 %, whileA. phagocytophilum was detected in 8.1 % ofI. hexagonus ticks. Only one nymph was positive forCand. N. mikurensis and none ofI. hexagonus ticks harbored aBabesia spp. Over 60 % ofD. reticulatus ticks were positive for rickettsial DNA, exclusively belonging to the speciesR. raoultii. Conclusion The high tick infestation rates and the prevalence of pathogens found in these ticks demonstrate a serious level of encounter to tick-borne diseases in urban dogs in the Wroclaw area, and provide evidence that dogs and cats themselves may substantially contribute to the circulation of the ticks and pathogens in the urban area.